Impact of DNA extraction techniques and sequencing approaches on microbial community profiling accuracy - Zoruk, Polina; Morozov, Maxim; Veselovsky, Vladimir; Strokach, Aleksandra; Babenko, Vladislav; Klimina, Ksenia (Frontiers in Microbiomes, 2025)
BackgroundQuality control in metagenomic data analysis is crucial for ensuring the accuracy and reliability of research results. Among the key steps in microbiome research, DNA extraction plays a critical role, as it directly determines DNA yield, integrity, and representation of microbial taxa.ResultsWe compared three commercial DNA extraction kits and our protocol specifically developed for the recovery of high molecular weight (HMW) DNA from complex microbial communities, using the ZymoBIOMICS Gut Microbiome Standard. The PureLin™ Microbiome DNA Purification Kit and our custom protocol provided superior recovery of DNA from Gram-positive bacteria, while the Wizard® kit and our protocol yielded HMW DNA suitable for long-read Oxford Nanopore sequencing. Among sequencing approaches, metagenomic sequencing on the Illumina platform provided the most accurate representation of the reference composition. However, all methods showed limited ability to detect taxa below 0.5% of relative abundance. Additionally, taxonomic classification based on 16S rRNA gene amplicon sequencing data misclassified closely related species due to high gene homology, a limitation not observed with metagenomic approaches.ConclusionsOur study establishes that a customized DNA extraction protocol is optimal for comprehensive microbiome studies utilizing long-read sequencing technologies. We show that metagenomic sequencing outperforms 16S rRNA gene amplicon sequencing for species-level accuracy, providing a validated benchmark for future gut microbiome research.